2017
DOI: 10.1162/jocn_a_01043
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of 10-Hz Repetitive TMS on Tasks of Visual STM and Attention

Abstract: Numerous studies have demonstrated that visual STM (VSTM) and attention are tightly linked processes that share a number of neuroanatomical substrates. Here, we used repetitive TMS (rTMS) along with simultaneous EEG to examine the causal relationship between intraparietal sulcus functioning and performance on tasks of attention and VSTM. Participants performed two tasks in which they were required to attend to or remember colored items over a brief interval, with 10-Hz rTMS applied on some of the trials. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…As mentioned above, Weber et al (2016) also showed that lower fMRI decoding of VWM content in left parietal area 7A was correlated with lower precision and higher precision variability measured in behavioral VWM performance. Consistent with the role of PPC in VWM storage, TMS to PPC affects VWM capacity (Emrich et al 2017).…”
Section: Visual Working Memory Representationsmentioning
confidence: 59%
“…As mentioned above, Weber et al (2016) also showed that lower fMRI decoding of VWM content in left parietal area 7A was correlated with lower precision and higher precision variability measured in behavioral VWM performance. Consistent with the role of PPC in VWM storage, TMS to PPC affects VWM capacity (Emrich et al 2017).…”
Section: Visual Working Memory Representationsmentioning
confidence: 59%
“…Further studies have shown the importance of baseline performance on the degree of change in other cognitive abilities using different forms of non-invasive brain stimulation (Krause and Cohen Kadosh, 2014, Benwell et al, 2015, Painter et al, 2015, Emrich et al, 2017, Penton et al, 2017, Yang and Banissy, 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, based on a growing literature showing that the effect of brain stimulation on behavioral tasks is highly variable across individuals (Jones et al, 2016, Palmer et al, 2016, Valchev et al, 2017 and might depend on a number of factors, including individual differences in the ability to perform the task (Krause and Cohen Kadosh, 2014, Benwell et al, 2015, Painter et al, 2015, Emrich et al, 2017, Penton et al, 2017, Yang and Banissy, 2017, we explored the contribution of individual differences in baseline EA task performance to performance changes induced by active rTMS. This allowed us to establish whether low-and high-performers in our EA task show any differential causal involvement of visual, sensorimotor and mentalizing brain areas in EA.…”
Section: Introductionmentioning
confidence: 99%
“…Single-pulse transcranial magnetic stimulation (TMS) applied over the human visual cortex induces illusory perceptions. Similarly to perceptions induced by visual stimuli, TMS-induced perceptions are most reliably triggered in a given phase of prestimulus alpha oscillations [42,43]. Providing causal evidence for the relationship between alpha phase and perception in the auditory modality, alphafrequency-modulated transcranial direct current stimulation (tDCS) biases the stimulusdetection threshold in a phase-dependent manner [44].…”
Section: Periodic Perceptual and Attentional Sampling Of Sensory Infomentioning
confidence: 99%